Prevalence of H Pylori Infection and Related Blood Biomarker among Autistic Children in Tobruk City, Libya - Fathia Bougafa, (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Neurological disorders have been linked to gastrointestinal (GI) abnormalities including a shift in gut microbiota. Helicobacter pylori bacteria plays an important role in progression and development of neurological diseases such as autism spectrum disorder (ASD). GI abnormalities in ASD children have been reported overseas, but there were not data for Libya. Therefore, the current study aims to assess the prevalence of H. pylori infection and related Blood Biomarker such as anemia among Autistic Children in Libyan population in particular in Tobruk City. Methods. The present participants recruited from the children ASD center in Tobruk city in the east of Libya with an age range 5-12years. H. pylori antigen were measured and the Iron deficiency (ID) parameters (hemoglobin content, hematocrit, MCH concentration) were also performed. Results. Seventy-eight % 78 of cases were positive for H. pylori antigen and hemoglobin and hematocrit level were low. Conclusion. H pylori infection and ID deficiency were prevalent among autistic children, which should be targeted during autism management.